Affective disorders, hospital admissions, and seasonal variation of mania in a subtropical area, southern hemisphere - Kerr-Correa, F.; Souza, L. B.; Calil, H. M. (Karger, 1998)
Hospital admissions (n = 15,450) to a state psychiatric hospital in Botucatu, São Paulo State, Brazil, over a 10-year period (1982-1991) were reviewed. 157 (1%) patients received a probable diagnosis of affective disorder according to DSM-III-R criteria. Among them, 46% had been diagnosed by the staff psychiatrists, and their diagnoses were sustained by the researchers, whereas 54% were diagnosed only by one of the researchers (F.K.C.). These last patients had previously received a diagnosis of paranoid schizophrenia or unspecified psychosis (ICD-9). Most of the patients with affective disorders were bipolar: 72 and 8%, respectively, presented manic and depressive episodes. Thus, only 20% received a diagnosis of major depression. A seasonal pattern in hospital admission was observed only for mania in women, their episodes occurring more often (p < 0.02) in spring and summer. No significant seasonal pattern in hospital admission for depression was found.